2003
DOI: 10.1051/0004-6361:20030884
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and kinematics of Lynds 1642

Abstract: Abstract. The high latitude translucent molecular cloud L1642 has been mapped in the J = 1-0 and J = 2-1 transitions of 12 CO, 13 CO and C 18 O using the SEST radio telescope. We have analysed the morphology and velocity structure of the cloud using the Positive Matrix Factorization (PMF) method. The results show that L1642 is composed of a main structure at radial velocity 0.2 km s −1 while the higher velocity components at ∼0.5 and 1.0 km s −1 form an incomplete ring around it, suggesting an expanding shell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…Laureijs et al (1987) showed that the radial density distribution ρ(r) follows the ρ(r) ∝ r −2 profile in the outer parts, and a flatter profile in the inner parts. A similar conclusion was drawn by Liljeström (1991) and Russeil et al (2003) from CO data. However, all these studies treated the cloud as a single unit, although it consists of several components.…”
Section: Introductionsupporting
confidence: 86%
“…Laureijs et al (1987) showed that the radial density distribution ρ(r) follows the ρ(r) ∝ r −2 profile in the outer parts, and a flatter profile in the inner parts. A similar conclusion was drawn by Liljeström (1991) and Russeil et al (2003) from CO data. However, all these studies treated the cloud as a single unit, although it consists of several components.…”
Section: Introductionsupporting
confidence: 86%
“…comm. ) is notably different than the cloud's CO emission at ≈0-1 km s −1 (Liljestrom 1991;Russeil et al 2003), perhaps due to spectroscopic binarity or unusual kinematics. Our proper motion measurement of (µ α , µ δ ) = (−0.6 ± 1.9, +9.3 ± 2.0) mas/yr is consistent with that of the IRASexcess star EW Eri associated with the cloud (Sandell et al 1987), which has a proper motion of (−5.3 ± 5.6, +7.1 ± 5.5 mas/yr) from UCAC4 (Zacharias et al 2013).…”
Section: Massi J0435145−141446 (M6δ/m7 Vl-g)mentioning
confidence: 77%
“…4. The contours of the column density map derived from the 13 CO data of Russeil et al (2003) are drawn in the optical depth map in Fig. 4 (left).…”
Section: Colour Temperature Optical Depth and Spectral Index Mapsmentioning
confidence: 99%
“…See Welsh & Shelton (2009) for a description of the Local Bubble. We adopted the distance of 140 pc similarly to Russeil et al (2003) and Lehtinen et al (2004). A&A 563, A125 (2014) L1642 has been studied using several molecules, see Liljestrom (1991) for a review of the early studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation